Triple combination of irinotecan + oxaliplatin + 5-fluorouracil as first-line chemotherapy for metastatic colorectal cancer: first experience with a new treatment regimen - A. D. Darenskaya; N. V. Dobrova (Тазовая хирургия и онкология, 2018)
Background. Despite the fact that treatment of metastatic colorectal cancer (mCRC) has undergone major advances in recent decades, long-term results remain unsatisfactory. Therefore, the development of new first-line therapeutic regimens for mCRC is an important challenge in current oncology. Objective: to assess the efficacy and safety of a novel therapeutic regimen containing irinotecan (Iri) + oxaliplatin (Oxa) + 5-fluorouracil (5-FU) in the first-line treatment of mCRC. Materials and methods. This prospective study included patients with mCRC that have never received therapy for disseminated tumors. All study participants were treated with a new first-line therapeutic regimen, developed by the Department of Chemotherapy and Combined Treatment of Malignant Tumors, Research Institute of Clinical Oncology, N.N. Blokhin Russian Cancer Research Center, Ministry of Health of Russia. This regimen includes a combination of Iri (100 mg/m2 body surface given as a 90-minute intravenous (IV) infusion on days 1 and 15) + Oxa (65 mg/m2 surface given as a 120-minute IV infusion on days 1 and 15) + 5-FU (200 mg/m2 /day, 14-days continuous IV infusion), than the patients had a treatment-free interval of 2 weeks followed by a new course starting from day 29. Results. In patients with multiple large visceral metastases, disease control (complete regression + partial regression + disease stabilization for >6 months) was achieved in 95 % of cases. The objective response rate (complete regression + partial regression) was 85 %. Median progression-free survival reached 10.8 ± 2.13 months (95 % confidence interval 6.62–14.98). Median overall survival in 20 patients has not yet been reached at a median follow-up time of 17.3 ± 2.54 months (95 % confidence interval 12.31–22.29). One-year overall survival was 88.9 %. During the study, we observed toxic effects typical of Iri, Oxa and 5-FU; in most of the cases, it was grade 1–2 toxicity. Grade 3 toxicity manifested primarily as neutropenia (14 % of courses). Neither grade 4 toxicity, nor episodes of febrile neutropenia were observed. None of the patients had to discontinue treatment due to unacceptable toxic effects. Conclusion. Our findings suggest high efficacy and safety of the new first-line triple-combination therapy with Iri + Oxa + 5-FU in patients with mCRC and unfavourable disease characteristics.